Enhancing Students' Writing Skills through Learning Models and Levels of Critical Thinking of Students - Suryadi, Suryadi; Fitriana, Meida (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aimed to investigate variations in English writing proficiency based on learning models (Project-Based Learning and Cooperative Learning) and students' critical thinking levels. Method: This research employs a quantitative methodology, notably utilising a quasi-experimental design. This design integrates the non-equivalent control group method with a two-way factorial design methodology (2 x 3 ANOVA). 300 students participated in this study. Each group consisted of one hundred and fifty-five students. All students were competent Indonesian speakers. The first experimental group was given the PjBL learning model, while the second group was given the cooperative learning model. The employed sampling method is random sampling Results: This study yielded three research findings: (1) disparities in writing proficiency among students adhering to distinct learning paradigms (PjBL versus Cooperative), evidenced by a significant value of F=6.921 and sig.<0.05 (2) Variations in writing proficiency among students classified according to high, medium, and low levels of critical thinking were significantly demonstrated with a F value of 5.836 and a significance level of p<0.05. (3) The interaction effect between learning models and students' critical thinking levels on writing skills was also significantly evidenced with a F value of 6.917 and a significance level of p<0.05. Novelty: The study’s novelty lies in its integrative approach simultaneously comparing two constructivist learning models while analyzing how critical thinking shapes their impact on writing skills. By bridging theoretical inquiry with pedagogical practice, this research contributes to the refinement of writing instruction, and the advancement of educational theory.